2009
DOI: 10.1091/mbc.e08-06-0662
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor-induced Phosphorylation of EphrinB1 Modulates Its Interaction with Dishevelled

Abstract: The Eph family of receptor tyrosine kinases and their membrane-bound ligands, the ephrins, have been implicated in regulating cell adhesion and migration during development by mediating cell-to-cell signaling events. The transmembrane ephrinB1 protein is a bidirectional signaling molecule that signals through its cytoplasmic domain to promote cellular movements into the eye field, whereas activation of the fibroblast growth factor receptor (FGFR) represses these movements and retinal fate. In Xenopus embryos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…Furthermore, activation of FGF signaling has a cell-autonomous role in controlling cell sorting in the mes. Finally, previous studies have shown that Fgfr1 is required for the expression of Cdh22, which encodes the cell adhesion molecule PB-cadherin, in the posterior mes (Trokovic et al, 2003), and that FGF signaling modulates ephrin and catenins in regulating cell-cell interactions (Lee et al, 2009;Lee et al, 2008;Lilien et al, 2002). As Fgf8-expressing cells form a tight transverse band in the isthmus, the mes cells immediately anterior to the MHB probably receive high levels of Fgf8 and thus display distinct cell adhesive characteristics.…”
Section: The Sorting Of Gbx2mentioning
confidence: 87%
“…Furthermore, activation of FGF signaling has a cell-autonomous role in controlling cell sorting in the mes. Finally, previous studies have shown that Fgfr1 is required for the expression of Cdh22, which encodes the cell adhesion molecule PB-cadherin, in the posterior mes (Trokovic et al, 2003), and that FGF signaling modulates ephrin and catenins in regulating cell-cell interactions (Lee et al, 2009;Lee et al, 2008;Lilien et al, 2002). As Fgf8-expressing cells form a tight transverse band in the isthmus, the mes cells immediately anterior to the MHB probably receive high levels of Fgf8 and thus display distinct cell adhesive characteristics.…”
Section: The Sorting Of Gbx2mentioning
confidence: 87%
“…Members of the ephrinB family are often overexpressed in cancer cells and are associated with angiogenesis and metastasis (45). Although several studies provide insight into how ephrinB1-mediated reverse signaling contributes to invasion of gastric and pancreas cancer cells (46,47), recent evidence reveals that intracellular domain of ephrinB1 interacts with Dvl and modulates PCP signaling to control cell adhesion and movement in development (48)(49)(50). This opens up the possibility to explore the potential crosstalk between ephrinB and PCP signaling in the context of tumor cell invasion and metastasis.…”
Section: Role Of Pcp Signaling In Tumor Metastasismentioning
confidence: 99%
“…The ephrinB1 DV mutant construct harbors a deletion of the conserved C-terminal valine that has been demonstrated to be critical for the binding of PDZ domain-containing proteins to both ephrin-B1 and ephrin-B2 (Lin et al 1999;Makinen et al 2005). It has been suggested that phosphorylation-dependent and PDZ-dependent reverse signaling may cooperate to achieve reverse signaling outcomes (Palmer et al 2002;Su et al 2004;Lee et al 2009). To address this possibility, we also generated a mutant mouse line in which the intracellular tyrosines Previous work has demonstrated the importance of proper membrane localization for evaluation of reverse signaling function Makinen et al 2005).…”
Section: Fmentioning
confidence: 99%